Determination of inductances for pulsating current traction motor - Goolak, Sergey; Tkachenko, Viktor; Sapronova, Svitlana; Spivak, Oleksandr; Riabov, Ievgen; Ostroverkh, Oleksandr (Technology audit and production reserves, 2021)
The object of research is a pulsating current traction motor. To improve the accuracy of its mathematical model, it is necessary to use the values of the parameters that are determined in experimental studies of the electric motor. In particular, it is important to use in the model of the electric motor inductance obtained experimentally. A method is proposed for calculating the inductance of the armature winding, main poles, additional poles and compensation winding and the total inductance of the traction motor armature circuit. The calculations are based on the results of the indirect inductance measurement method, in which the electrical values of various modes of power supply of the electric motor windings are directly measured, and the inductances are determined by auxiliary calculations. The inductances of the traction motor armature circuit have a non-linear dependence on the current flowing through them. The main difference of the study is that the measurements of the electrical parameters required for calculating the inductance are carried out over the entire range of operating currents of the windings. The essence of the proposed technique is to measure the active power in the armature winding, the winding of the main and additional poles, and the compensation winding, as well as in the armature circle as a whole when they are supplied with alternating current. According to the obtained values of active power losses and phase displacement, the corresponding reactive power losses are determined, with the help of which the inductances of the motor windings are calculated. Approbation of the methodology for calculating the conduction inductance for an electric motor of a pulsating current NB-418K6 (country of origin Russia), is used on electric locomotives of the VL80T and VL80k series (country of origin Russia). A scheme for measuring electrical parameters necessary for calculating inductance is proposed. The graphical dependences of the inductance on the armature current, built on the basis of calculations, confirmed the hypothesis about the nonlinear dependence of these inductances on the armature current. For further application of the results obtained in the simulation of the operation of the traction electric motor NB-418K6, a polynomial approximation of the total inductance of the armature circuit was performed.